ANALYSIS OF WILLINGNESS TO PAY OF BANDUNG CITY COMMUNITY TOWARDS WASTE SERVICES - Sapto Prajogo (Journal of Research in Social Science and Humanities, 2025)
The Leuwigajah landfill collapse disaster has left dark memories for the people of Bandung. After the incident occurred, the area in the Greater Bandung area practically no longer had a landfill. In a matter of days, almost all corners of Bandung City were filled with garbage. The dark incident finally began to return to normal when the government opened the Sarimukti landfill. The garbage could finally be transported to the Sarimukti landfill. The people of Bandung City realized the importance of urban waste management. This study aims to identify the characteristics of the people of Bandung City, who are consumers of urban waste management services. Calculating the willingness to pay (WTP) for urban waste management. WTP in the people of Bandung City is based on the type of settlement. The results of this study show that the average WTP value in dense settlements is Rp. 2,978, - / capita / month, the average WTP in non-dense settlements is Rp. 9,386, - / capita / month